2006
DOI: 10.1021/bi061626q
|View full text |Cite
|
Sign up to set email alerts
|

Specific and Efficient Binding of Xeroderma Pigmentosum Complementation Group A to Double-Strand/Single-Strand DNA Junctions with 3‘- and/or 5‘-ssDNA Branches

Abstract: Human XPA is an important DNA damage recognition protein in nucleotide excision repair (NER). We previously observed that XPA binds to DNA lesion as a homodimer (1). Herein we report that XPA recognized undamaged DNA doublestrand/ single-strand (ds-ssDNA) junctions containing ssDNA branches with binding affinity (K d = 49.1±5.1 nM) much higher than its ability to bind to DNA damage. The recognized DNA junction structures include Y-shape junction (with both 3′-and 5′-ssDNA branches), 3′-overhang junction (with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
57
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 59 publications
(67 citation statements)
references
References 45 publications
10
57
0
Order By: Relevance
“…NER (17,18). Several reports have shown that XPA mediates the initial recognition and verification of DNA lesions, stabilizes repair intermediates, and is involved in the induction of other NER factors (19)(20)(21)(22)(23)(24). Therefore, it is likely that upregulation of XPA expression would increase platinum resistance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…NER (17,18). Several reports have shown that XPA mediates the initial recognition and verification of DNA lesions, stabilizes repair intermediates, and is involved in the induction of other NER factors (19)(20)(21)(22)(23)(24). Therefore, it is likely that upregulation of XPA expression would increase platinum resistance.…”
Section: Discussionmentioning
confidence: 99%
“…The xeroderma pigmentosum complementation group A (XPA) protein is an indispensable factor for NER. Several reports have shown that XPA recognizes and verifies DNA damage sites, stabilizes repair intermediates, and contributes to the induction of other NER-associated factors (19)(20)(21)(22)(23)(24) (17)(18)(19)(20)(21)(22)(23)(24)(25). However, the role of XPA in the response of uterine cervical cancer cell lines and uterine cervical cancer patients to cisplatin is not clear.…”
Section: Introductionmentioning
confidence: 99%
“…30 A recent in vitro study has suggested that the high affinity of XPA for the damage site may not be dependent on the damaged base but rather on the preincision DNA structures generated by local unwinding of the DNA surrounding the damage. 31 Thus, XPA may play a structural role in maintaining the pre-incision DNA bubble and positions the remaining NER factors, particularly XPF-ERCC1, 30 for final incisions while RPA may protect the undamaged strand (which will be used as the template for re-synthesis following incisions) from nuclease attack. 32 Other XPA interacting proteins include ATR (ATM and RAD3-Related), 33 a DNA damage checkpoint kinase of the phosphoinositide 3-kinase-like kinase (PIKK) family, XAB1 (XPA-binding protein 1) 34,35 and XAB2 (XPA-binding protein 2).…”
Section: Finding Dna Damage: Xpa Xpc and Xpementioning
confidence: 99%
“…XPC is then needed for the recruitment of the core NER repair factors XPA, TFIIH, and RPA (Evans et al, 1997;Araujo et al, 2001;Thoma and Vasquez, 2003). XPA and the basal transcription factor complex TFIIH bind to the damaged site and unwind the DNA around the lesion (Reardon and Sancar, 2003;Maltseva et al, 2006;Yang et al, 2006;Kesseler et al, 2007;Krasikova et al, 2008). Unwinding is specifically performed by two subunits of TFIIH, the helicases XPB (ERCC3) and XPD (ERCC2).…”
Section: Nucleotide Excision Repairmentioning
confidence: 99%
“…Unwinding is specifically performed by two subunits of TFIIH, the helicases XPB (ERCC3) and XPD (ERCC2). RPA is a heterotrimeric DNA binding protein, and while it prevents incision of the non-damaged DNA strand, together with XPA, it stabilizes the opened double helix (Blackwell et al, 1996;Camenisch et al, 2006;Maltseva et al, 2006;Yang et al, 2006). Incisions are performed by the endonucleases XPF (ERCC1) and XPG which nick the damaged DNA strand 5' and 3' around the lesion.…”
Section: Nucleotide Excision Repairmentioning
confidence: 99%